International multidisciplinary consensus on the definition and clinical approach for monogenic inflammatory immune dysregulation disorders - Hend M. Alkwai; Ibrahim A. Almaghlouth; Leonardo Oliveira Mendonça; Shuayb Elkhalifa; Hassan Abolhassani; Suliman Aljumaah; Hamoud Al-Mousa; Mohammed F. Alosaimi; Alhanouf AlSaleem; Tadej Avcin; Winnie KY Chan; Graciela Espada; et al. (Pediatric Rheumatology Online Journal)
Abstract Objective To achieve consensus on the definition and clinical approach of Monogenic Inflammatory Immune Dysregulation Disorders (MIIDDs), a collective term for rare conditions marked by inflammation, immune dysregulation, and infection susceptibility. These consensus guidelines specifically apply to pathogenic (or likely pathogenic) gene mutations affecting both innate and adaptive immunity, excluding variants of unknown significance (VUS). Methods A multi-step, evidence-based, multidisciplinary consensus process was employed, consisting of: (1) a systematic literature review across four electronic databases (Cochrane Library, Web of Science, Scopus, and MEDLINE via PubMed), updated through December 31, 2024; (2) a pre-Delphi electronic survey completed by 95 international adult and pediatric immunologists and rheumatologists; and (3) a modified online Delphi process with an international multidisciplinary expert panel, where statements were iteratively analyzed and refined until achieving consensus (≥ 80% agreement among panelists). Results Fifteen experts from 12 countries participated in two rounds of the Delphi process, resulting in the development of eight overarching principles and 10 consensus statements. These were categorized into five domains: (1) definitions and conceptual framework, (2) diagnostic and monitoring considerations, (3) treatment and therapeutic strategies, (4) multidisciplinary and collaborative care, and (5) patient education and support. Conclusion This consensus defines MIIDDs and provides a structured clinical framework to streamline research efforts and improve patient outcomes.